Modelling the widths of fission observables in GEF - Schmidt K.-H.; Jurado B. (EPJ Web of Conferences, 2013)
The widths of the mass distributions of the different fission channels are traced back to the probability distributions of the corresponding quantum oscillators that are coupled to the heat bath, which is formed by the intrinsic degrees of freedom of the fissioning system under the influence of pairing correlations and shell effects. Following conclusion from stochastic calculations of Adeev and Pashkevich, an early freezing due to dynamical effects is assumed. It is shown that the mass width of the fission channels in low-energy fission is strongly influenced by the zero-point motion of the corresponding quantum oscillator. The observed variation of the mass widths of the asymmetric fission channels with excitation energy is attributed to the energy-dependent properties of the heat bath and not to the population of excited states of the corresponding quantum oscillator.